Europeanisation as empowerment of civil society: all smoke and mirrors? - Parau, C; Bains, J (Edward Elgar Publishing, 2008)
Introduction: Despite an explosion of research into the ﬁeld of Europeanisation in recent years, the outcomes and processes that constitute it remain empirically underexplored, particularly in the context of the newly acceded EU Member States of Central and Eastern Europe (CEE). This chapter endeavours partly to to ﬁll this gap by exploring Europeanisation through a ‘bottom-up’ lens, asking which domestic actors get empowered and how they utilise the opportunities and avoid the constraints created by the EU at the domestic level. These questions are examined through three cases studies of a series of domestic controversies over public accountability and input legitimacy. The case studies are drawn from (at the time of writing): a current Member State, the UK; a new Member State (a leading EU accession candidate), the Czech Republic, and a poorly performing EU accession candidate, Romania (now a Member State). The cases studied are genetically modiﬁed organisms (GMO) legislation in the Czech Republic; the South East London combined heat and power incinerator in the United Kingdom;1 and the Transylvanian motorway in Romania. These case studies will shed light on how domestic civil society and government utilise the EU and its new opportunities in political contests aimed at inﬂuencing domestic policy making, and ultimately altering domestic power relations.